Endotypes and Phenotypes in ILD: Is It Time to Reclassify ILD by Risk Stratification? - Francesco Amati; Anna Stainer; Stefano Aliberti (Biomedicines)
Interstitial lung diseases (ILD) comprise a heterogeneous group of disorders that present significant challenges in both diagnosis and management due to their varied nature, which encompasses different degrees of inflammation and fibrosis affecting lung tissue [...]